Atomic force microscopy studies of thermal, mechanical and velocity dependent wear of thin polymer films - Rice, Reginald H. (Kansas State University, 2012)
Nanoscale modifications of polymer surfaces by scratching them with sharp tips with curvature radii of tens of nanometers and at variable temperatures are expected to provide wealth of information characterizing wear response of these polymers. Such studies are important in the light of understanding the nanoscale behavior of matter for future applications in advanced polymer coatings. This thesis describes how Atomic Force Microscopy (AFM) and hot-tip AFM (HT-AFM) methods were used to characterize thermal and mechanical properties of a 30 nm thick film of poly(styrene-block-ethylene oxide), PS-b-PEO, and modify its lamellar surface patterns. Additionally, it is revealed how contact AFM and HT-AFM methods can efficiently characterize the wear response of two popular polymer surfaces, poly(methyl methacrylate), PMMA, and polystyrene, PS. The AFM and HT-AFM studies on PS-b-PEO copolymer were aimed at producing spatial alignment of respective PS and PEO parts. Instead, however, surface ripples were obtained. These measurements are explained using mode I crack propagation model and stick-and-slip behavior of an AFM tip. In addition, HT-AFM studies allowed extraction of several thermo-physical properties of a PS-b-PEO film at local volumes containing about 30 attograms of a polymer. These thermo-physical quantities are: PEO melting enthalpy of, 111 ± 88 J g[superscript]-1, PS-b-PEO local specific heat of 3.6 ± 2.7 J g[superscript]-1K[superscript]-1, and molecular free energy of Helmholtz of 10[superscript]-20 J nm[superscript]-2 for the PEO within PS-b-PEO. Utilizing a spiral scan pattern at constant angular speed and at various temperatures at the AFM tip-polymer interfaces, the wear response of PS and PMMA polymers was characterized. Cross-sections along the obtained spiral wear patterns provided plots of polymer corrugation as a function of scanning speed. From these studies it was found that the corrugation of the modified polymer surface decays exponentially with linear velocity of the scanning tip.
Keywords: AFM; Copolymers; Hot tip; Materials Science (0794); Physics (0605)